Economic and production costs analysis of the dairy activity during 10 years in a property of the upper jequitinhonha valley - De Assis, Leandro Pereira; Villela, Severino Delmar Junqueira; Lopes, Marcos Aurélio [UNESP]; Dos Santos, Roseli Aparecida; Resende, Elton Silva; Silvestre, Luiz Henrique Aparecido; Silva, Helenita Bárbara Fonseca; Martins, Paulo Gustavo Macedo De Almeida (My University, 2017)
The objective was to analyze the economic performance of a dairy enterprise, located in Couto de Magalhães de Minas, municipality of the Jequitinhonha valley in Minas Gerais, between the period from January 2002 to December 2011. Specifically, it was intended to estimate the representativeness of the components of the effective operational cost and the total cost of production, the breakeven point, and present possible solutions to reduce production costs. The data, which were recorded in a software for management of expenses and income, were tabulated in electronic sheets especially developed for this purpose. The economic results of gross margin, net margin (profit/loss), considered as indicators of economic efficiency, were evaluated. Among the components of the effective operational cost, feeding and labor had higher representativeness. The average revenue from only the milk sale was not enough to cover the actual operating costs. However, when summed with the revenues from the animals’ and by-products’ sale, the revenue allowed, on the average of ten years, gross and net positive margins, the production system being capable of accumulating a capital reserve fund used to replace depreciated production assets, not condemning the production assets to the scrapping.
Keywords: Dairy activity; Economic viability; Production costs